Moroccan speleothem and tree ring records suggest a variable positive state of the North Atlantic Oscillation during the Medieval Warm Period - Wassenburg, Jasper; Immenhauser, A.; Richter, D. K.; Niedermayr, A.; Riechelmann, S.; Fietzke, J.; Scholz, Denis; Jochum, K. P.; Fohlmeister, Jens; Schröder-Ritzrau, Andrea; Sabaoui, A.; Riechelmann, Dana; et al. (Earth and planetary science letters, 2013)
We present a magnesium (Mg) and strontium (Sr) record from an aragonitic speleothem (Grotte de Piste, Morocco, 34°N; 04°W) providing a reconstruction of effective rainfall from 619 to 1962 AD. The corresponding drip site was monitored over 2yr for drip water Mg/Ca and Sr/Ca ratios. Results show evidence for prior aragonite precipitation, which can explain negative correlations between speleothem Mg and Sr concentrations. The data shown here have important climate implications concerning the evolution of the North Atlantic Oscillation (NAO). A comparison of the stalagmite data from Grotte de Piste with an updated tree ring based drought reconstruction from Morocco and other NAO related proxy records confirms that the Medieval Warm Period (MWP) was dominated by NAO+ conditions. The stalagmite record and multiple proxy records from the Iberian Peninsula, however, suggest that considerable rainfall variability occurred during the MWP. This implies that the NAO has been more variable during the MWP than formerly suggested.
Gesehen am 30.09.2021